PENGARUH KEPEMIMPINAN, KOMPENSASI KERJA, MOTIVASI PELAYANAN TERHADAP KINERJA GURU YAYASAN MARDI WIYATA MALANG MELALUI KEUNGGULAN NILAI - Mere, Klemen - (Magister Manajemen Universitas Wisnuwardhana, 2015)
Abstract: The analysis showed that there was no significant effect of leadership on the value of excellence. There are no direct influence between leadership on teacher performance Foundation Mardi Wiyata Malang through excellence value. There is a positive and significant direct effect between labor compensation to the value of excellence. There is a compensation effect between the work on teacher performance through excellence in value. There is a significant influence between motivation of service to the value of excellence. There is a significant relationship between motivation of service to the Foundation Mardi Wiyata teacher performance through excellence in value. There is a significant relationship between the value of the performance advantages of teachers Mardi Wiyata Foundation. Keywords: Leadership, work compensation, service motivation, teacher performance, superior value